Exploring dilemma games in sustainable urban planning: A Cypriot case study on urban rooftop utilization for climate change - Merry Anna; Zachariou Aravella; Yau Jane (E3S Web of Conferences)
This paper describes the initial stages of a Cypriot case study on urban rooftop utilization for climate change, indicating how games can: foster collaboration; engage citizens; and produce policy incentives through real-world exploration and implications. The focus of the case study is a co-designed serious game developed within the context of the GREAT project (Games Realizing Effective and Affective Transformation) to be utilized as a facilitation tool between citizens and policy makers. Through learning and role-play scenarios, target groups can: voice their attitudes towards climate policies; gain valuable insights into specific initiatives; and enhance their acceptance of green infrastructure and sustainable urban planning. In this paper, we describe the initial co-design stages of the dilemma game, discuss the lessons learned, and provide future directions for research.